Nutrient availability affected by silicate and Azospirillum brasilense application in corn–wheat rotation - Galindo, Fernando Shintate; Pagliari, Paulo Humberto; Buzetti, Salatiér [UNESP]; Rodrigues, Willian Lima [UNESP]; Fernandes, Guilherme Carlos [UNESP]; Biagini, Antônio Leonardo Campos [UNESP]; Tavanti, Renan Francisco Rimoldi [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Wiley, 2021)
The interactive effectof silicon (Si) application on soil fertility is poorly understood when inoculation with Azospirillum brasilense is performed. This research determined if Si application and A. brasilense inoculation to corn (Zea mays L.) and wheat (Triticum aestivum L.) has agronomic benefits on soil nutrient concentration and grain yield. Treatments were tested under a no-till system in a Rhodic Haplustox in a full factorial design with four replicates and comprised (a) two soil amendment sources—calcium (Ca) and magnesium (Mg) silicate and dolomitic limestone; (b) with and without seed inoculation with A. brasilense; and (c) five sampling dates collected during two corn–wheat crop rotations (2015–2017). Calcium and Mg silicate application was effective at decreasing soil hydrogen + aluminum (H+Al) and Al content and increasing soil pH, sum of bases, and base saturation. However, silicate changed soil nutrient availability, reduced cation exchange capacity, phosphorus (P) and Mg content and did not significantly affect (p >.05) corn and wheat grain yield. Inoculation reduced Al toxicity, with lower H+Al and Al contents, and increased K content, leading to a greater pH and base saturation after four cropping seasons. Inoculation increased corn and wheat grain yield by 8.2 and 8.3%, respectively. Application of Ca and Mg silicate was more effective than limestone as a liming agent but could result in decreased availability of certain nutrients in soil. Inoculation with A. brasilense could be an important management practice to maintain adequate Si content in soil when limestone is applied. However, with silicate application, A. brasilense could increase Si depletion in soil.